Causal Relationships Between Total Physical Activity and Ankylosing Spondylitis: A Mendelian Randomization Study - Hu, Shaojun; Xing, Hongyuan; Wang, Xingchen; Zhang, Ning; Xu, Qiang (Frontiers in Immunology, 2022)
Background: Currently, there is little literature about the association between physical activity (PA) and the risk of ankylosing spondylitis (AS). The present study aimed to understand the causal relationships between PA and AS. Methods: We performed two-sample Mendelian randomization (TSMR) using publicly released genome-wide association studies summary statistics to estimate the causal associations of PA with AS risk. The inverse variance weighted (IVW) method was utilized as primary TSMR analysis. Furthermore, sensitivity, pleiotropy and heterogeneity analyses were then conducted to assess the robustness of the findings of the present study. Results: Results of the IVW analysis suggested a protective relationship between accelerometer-based PA and AS (average acceleration, odds ratio [OR] = 0.9995, 95% CI, 0.9988-0.9999, P = 0.014). On the contrary, there was no causal relationship between accelerometer-based PA (acceleration fraction > 425 milligrams; OR = 0.9981, 95% CI = 0.9936-1.0026, P = 0.402) and AS. Furthermore, there was no significant relationship between self-reported vigorous PA and AS (OR = 1.0005, 95% CI = 0.9875-1.0136, P = 0.943), or even between self-reported moderate-to-vigorous PA and AS (OR = 1.0000, 95% CI, 0.9947-1.0052; P = 0.990). Conclusions: the use of genetic approach in the present study revealed that total physical activity (TPA) has a protective relationship with AS risk. Further, it was evident that vigorous PA or moderate-to-vigorous physical levels are not causally associated with AS. Therefore, the present study evidently supports the hypothesis that enhancing TPA rather than PA intensity is an effective prevention strategy for AS.